From Cambridge to Lake Chad : life in archaeology 1956-1971 - Connah, Graham (Archaeological lives, 2019)
This title is about how the author became an archaeologist at a time when opportunities for employment were rare and how he worked as a field researcher in West Africa and wrote about his work there. It traces his archaeological training and employment at Cambridge and his practical experience on British excavations and explains how he became one of the pioneers of Nigerian archaeology during a decade in that country. It is not so much a study of the archaeology that was done, as an account of how it was done; its circumstances, organization, and economic and social and cultural context. As a result, it is both a professional and personal account, for these two aspects of life were inseparably intertwined, his wife Beryl becoming an integral part of the story. Other archaeologists and many non-archaeologists also feature in the account